Platon und das Schöne - Männlein-Robert, Irmgard; Corcilius, Klaus (Mohr Siebeck, 2022)
Plato and the Beautiful.
PublicationDate: 20230227
Keywords: Ästhetik -- Metaphysik -- das Hässliche -- AkkoandDor -- Antike Philosophie -- Array